Implementasi Model Pembelajaran Contextual Teaching and Learning (Ctl) dalam Proses Pembelajaran di Sekolah Dasar - Ira Maulina; Yuni Setia Ningsih; Fahrul Rijal (Universitas Palan, 2024)
The problem of education, especially in learning, is the low quality, relevance, and efficiency of learning so that the responsiveness and comprehension of students are very low. A learning approach is needed that fosters creativity and innovation in students, namely through the application of Contextual Learning (PKB). This article aims to explain the concept of implementing the Contextual Learning (PKB) model in the educational process in elementary schools. Contextual learning is an educational approach that allows instructors to connect learning materials with real-world scenarios and their relevance in the role of students as family members, citizens, and employees, while fostering active participation in the learning tasks required. The contextual approach (PKB) must be applied, because education is still dominated by the perception that knowledge consists of facts that require memorization. In this scenario, the function and role of the teacher remain dominant, so that students become obedient and uncreative. Students are expected to learn from personal experience rather than memorizing through this contextual approach. PKB emphasizes the importance of student involvement in finding material, highlights the importance of direct experience, and does not anticipate that students only absorb lessons; instead, PKB encourages students to actively seek learning resources. CTL improves students' ability to apply knowledge in real life, which shows that CTL not only aims for students to understand the topic but also understand how the topic affects their behavior in everyday life.